Coarsening of skeletal microstructures: Re-examination of data on Pseudo-Skeletal γ′ precipitate coarsening in binary Ni-Al Alloys. (1st July 2022) - Ardell, Alan J.
ABSTRACT: Skeletal microstructures are dispersed contiguous phases, morphologically complex and frequently characterized using the average area per unit volume, S –1, which has units of length and is measurable using stereological methods. Results published nearly two decades ago on the kinetics of coarsening of γ′ precipitates in binary Ni-Al alloys are re-examined. The microstructures in those alloys were palpably non-skeletal. S –1 was measured as a function of time to obtain data on the variation of the rate constant for coarsening as a function of γ′ volume fraction. An unfortunate error was made in the conversion of units which negates all the conclusions of that investigation. Re-analysis of those data demonstrates that the equations describing skeletal coarsening kinetics cannot be trusted to provide useful quantitative information on coarsening of non-skeletal microstructures and the role of elastic energy engendered by coherent, misfitting γ′ precipitates. Graphical abstract: Image, graphical abstract